Application of Cobalt Chloride and Silver Nitrate for Efficient Microspore Culture of Brassica rapa ssp. (Plant Tissue Culture and Biotechnology, 2013)
The effects of ethylene antagonistic cobalt chloride and silver nitrate, on microspore embryogenesis were investigated using three different concentrations in the medium for three Korean cultivars (two non-heading and one heading) of Brassica rapa ssp. Inclusion of cobalt chloride (5 μM ) in the culture medium significantly improved embryo production in the non-heading cultivar (33 embryos/bud) with embryo yields being increased up to 32%. The addition of silver nitrate (0.1 mg/l) to the culture medium also showed a progressive increase in embryo yields in the non-heading cultivar (34 embryos/bud) with embryo yields being increased up to 36%. For the heading cultivars, the highest embryogenic response was 2.8 embryos/bud (Jo saeng Miho), following the addition of silver nitrate (0.1 mg/l) to the culture medium, whereas 2.4 embryos/bud were observed with the addition of 5 μM cobalt chloride to the culture medium.Plant Tissue Cult. & Biotech. 23(1): 1-10, 2013 (June)